DISCHARGE PLANNING DAN PELATIHAN PEMANTAUAN STATUS GIZI BERBASIS DIGITAL BAGI ORANG TUA ANAK KANKER PASCA KEMOTERAPI DI YKAKI SEMARANG - Anna Kurnia; Erna Sulistyawati; Sri Hapsari Suhartono Putri; Fella Nurdini; Aisyah Nur Fadhila Nugraha (Universitas Mataram, 2026)
Among children with cancer receiving chemotherapy, malnutrition is a serious issue. Malnutrition is more likely when chemotherapy side effects like nausea, vomiting, and decreased appetite result in insufficient nutritional intake. This illness can lower the child's quality of life, lengthen the course of treatment, and raise the risk of infection. It is necessary to address the issue of parents' inadequate understanding of safe and sufficient meal types, quantities, and frequency following hospital release. The purpose of this program is to provide structured education, training, and mentorship to parents at the Rumah Kita of Yayasan Kasih Anak Kanker Indonesia (YKAKI) Branch of Semarang in order to avoid malnutrition in children following chemotherapy. Twelve parents accompanied the kid patients, and five halfway home managers participated in the activities. Outreach, nutrition education, training in digital technology-assisted nutritional status measurement, and pre- and post-test monitoring and evaluation were among the implementation strategies. Parents' awareness increased from 78% to 88%, and managers' abilities improved from initially being limited to one type of nutritional status measurement to five types of measurements in compliance with WHO guidelines. Additionally, a daily meal cycle designed to meet the dietary requirements of kids with cancer was offered. This program boosted the shelter's discharge planning system and helped families better identify and satisfy the nutritional needs of their children. The success of the initiative showed that working together, the parents, shelter management, and medical staff can prevent malnutrition and enhance the quality of life for children with cancer who have undergone chemotherapy. In conclusion, discharge planning helped parents meet their children's dietary needs by providing a daily food cycle. Training in nutritional status monitoring enhanced managers' capacity to keep an eye on kids' nutritional health.